Zonally Magnified Oblique Multislice and Non-Zonally Magnified Oblique Multislice DWI of the Cervical Spinal Cord - Alizadeh, M.; Poplawski, M.M.; Fisher, J.; Gorniak, R.J.T.; Dresner, A.; Mohamed, F.B.; Flanders, A.E. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: The zonally magnified oblique multislice EPI (ZOOM-EPI) diffusion-weighted sequence has been visually shown to provide superior MR diffusion image quality compared with the full-FOV single-shot EPI sequence (non-ZOOM-EPI) in the adult cervical spinal cord. The purpose of this study was to examine the diffusion tensor imaging indices in the normal human cervical spinal cord between ZOOMED and non-ZOOMED DTI acquisitions and determine whether DTI values are comparable between direct and indirect age-matched groups.MATERIALS AND METHODS: Fifty-four subjects 23–58 years of age (9 direct age-matched and 45 indirect age-matched) were scanned using a 1.5T scanner. Diffusion tensor indices including fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity were generated from the DTI dataset. These DTI values were calculated for both ZOOM and non-ZOOM acquisitions and compared at each intervertebral disc level. The variability of the DTI values for ZOOM and non-ZOOM sequences was measured using a coefficient of variation within direct and indirect age-matched controls.RESULTS: The mean diffusivity, axial diffusivity, and radial diffusivity values obtained along the cervical spinal cord in the age-matched controls showed a significant decrease using the ZOOM sequence (P = .05, P = .002, and P < .001). Mean fractional anisotropy showed a significant increase (P = .04) using the ZOOM sequence. The indirect age-matched controls showed a statistically significant increase in fractional anisotropy (P = .03) and a decrease in mean diffusivity (P = .002), axial diffusivity (P < .001), and radial diffusivity (P = .002) using the ZOOM sequence. Less variability has been shown in DTI using the ZOOM sequence compared with the non-ZOOM sequence in both direct and indirect age groups. The ZOOM sequence exhibited higher SNR (SNRZOOM = 22.84 ± 7.59) compared with the non-ZOOM sequence (SNRnon-ZOOM = 19.7 ± 7.05). However, when we used a 2-tailed t test assuming unequal variances, the ZOOM sequence did not demonstrate a statistically significant increase.CONCLUSIONS: ZOOM DTI acquisition methods provide superior image quality and precision over non-ZOOM techniques and are recommended over conventional full-FOV single-shot EPI DTI for clinical applications in cervical spinal cord imaging.ADaxial diffusivityCoVcoefficient of variationFAfractional anisotropyMDmean diffusivityRDradial diffusivityZOOMzonally magnified oblique multislice